2007
DOI: 10.1002/jbt.20151
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of rutin on lipids, lipoproteins, and ATPases in normal and isoproterenol‐induced myocardial infarction in rats

Abstract: The present study was designed to evaluate the preventive role of rutin on lipids, lipoproteins, and ATPases in normal and isoproterenol (ISO)-induced myocardial infarction in rats. Rutin (40 and 80 mg/kg) was orally administered to rats for a period of 42 days. After that period, isoproterenol (150 mg/kg) was injected subcutaneously to male wistar rats at an interval of 24 h for 2 days. The weight of heart and the concentrations of total cholesterol, triglycerides, and free fatty acids were increased signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 20 publications
2
13
1
Order By: Relevance
“…This elevated lipid alters enzymatic permeability and increased lipid synthesis by cardiac cAMP (Stanely Mainzen Prince and Karthick, 2007). In the present study, fall in HDLcholesterol level and elevation of total cholesterol and LDL-cholesterol levels was observed and this results are in line with earlier reports (Kumar et al, 2011;Stanely Mainzen Prince and Karthick, 2007).…”
Section: Discussionsupporting
confidence: 95%
“…This elevated lipid alters enzymatic permeability and increased lipid synthesis by cardiac cAMP (Stanely Mainzen Prince and Karthick, 2007). In the present study, fall in HDLcholesterol level and elevation of total cholesterol and LDL-cholesterol levels was observed and this results are in line with earlier reports (Kumar et al, 2011;Stanely Mainzen Prince and Karthick, 2007).…”
Section: Discussionsupporting
confidence: 95%
“…The outcomes of the present study are in a sharp discrepancy with those of two studies of Karthick and Stanely Mainzen Prince (Karthick and Stanely Mainzen Prince, 2006;Stanely Mainzen Prince and Karthick, 2007). In their experiments, animals were pretreated for 42 days with rutin using intragastric tube and then ISO in a dose of 150 mg kg −1 s.c. was administered once daily for 2 days.…”
Section: Discussioncontrasting
confidence: 61%
“…Indeed, previous studies have suggested very promising effects of rutin on ISO-induced cardiac injury in rats. Rutin, administered orally for 42 days, significantly improved both changes in the levels of lipids, lipoproteins and activity of Ca 2+ -dependent Na + /K + ATPase (Stanely Mainzen Prince and Karthick, 2007) as well as it reduced lipid peroxidation and increased myocardial antioxidative defence (Karthick and Stanely Mainzen Prince, 2006). The observed effects have been attributed to the antioxidant potential of rutin.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, EGCG protected the myocardium against the deleterious effects of lipids in experimentally induced MI. Previous studies also showed that antioxidants such as rutin and naringin prevented the accumulation of lipids in ISO-treated rats [36,37].…”
Section: Discussionmentioning
confidence: 91%